Left ventricular septal pacing: how deep is enough?. (19th May 2022) - Curila, K; Jurak, P; Waldauf, P; Halamek, J; Stros, P; Smisek, R; Plesinger, F; Znojilova, L; Leinveber, P; Viscor, I; Herman, D; Osmancik, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Charles University Research Program Background: When pacing in the left septal area, it is not clear where the pacing lead needs to be implanted to obtain the most physiological ventricular activation during pure myocardial pacing. Objective: To use UHF-ECG to compare ventricular activation between myocardial pacing of the left septum with and without the possibility to capture the left bundle branch by high output pacing. Methods: This was a retrospective study of patients with bradycardia and deep septal myocardial pacing close to LBB (paraLBBP) or deep septal pacing more distant from LBB (DSTP), which both produced a pseudo-right bundle branch morphology in V1. During paraLBBP, left bundle branch capture was feasible during increasing pacing output up to 5V at 0.5 ms, but during DSTP, LBB capture was not possible during high output pacing. Only patients with both paraLBBP and DSTP were analyzed. Paced QRS morphology, presence of LBBpotential, QRSduration, R wave peak time (RWPT) in V5, lead depth in the septum and UHF-ECG parameters of dyssynchrony, i.e., e-DYS as the difference between the first and last ventricular activation and local depolarization durations in precordial leads (V1-V8d) were compared between them. Results: From 119 consecutive bradycardia patients enrolled, we identified 23 with both paraLBBP and DSTP during an implant procedure. On X-ray, a lead tip was placed shallower during DSTP than paraLBBP (12 ± 3 vs. 15 ± 3 mm, p < 0.001). A pseudo right bundle branch block morphology was present in all cases, but LBB potential was more frequently present in paraLBBP (17 of 23) than in DSTP (4 of 36; p < 0.0001). QRSd was not significantly different (146 ± 14 vs. 142 ± 14 ms, p = 0.08), but DSTP had longer V5RWPT (86 ± 11 vs. 83 ± 9 ms; p = 0.03). paraLBBP resulted in larger interventricular dyssynchrony, e-DYS (-20 ± 15 vs. -12 ± 18 ms; p = 0.046), the same V1-6d, but its local depolarization durations in V7 and V8 (V7 and V8d) were shorter compared to DSTP (-5 and -7 ms; p < 0.05). Conclusion: Interventricular dyssynchrony and LV lateral wall depolarization during myocardial pacing of the left septum are dependent on the relation of the leads´ tip to the LBB. Pacing positions closer to the LBB are responsible for bigger interventricular dyssynchrony and more physiological LV lateral wall depolarization.